A comparative study of the influence of the content and source of β-glucan on the rheological, microstructural properties and stability of milk gel during acidification. (April 2021) - Aljewicz, Marek; Mulet-Cabero, Ana-Isabel; Wilde, Peter J.
Abstract: The aim of the study was a comprehensive, comparative study evaluating the impact of the addition level (0.125%, 0.25%, 0.5%, 1%) of highly purified β-glucans isolated from bacteria (curdlan), fungi (scleroglucan) and oats on the stability, rheological and microstructural properties of milk gel during acidification with glucono-δ-lactone. Viscosity and susceptibility to shear thinning were lowest in aqueous solutions containing oat β-glucan (OBG) and highest in solutions containing curdlan. Regardless of their addition level, curdlan and scleroglucan produced pseudoplastic fluid. Coagulation was most rapidly induced by scleroglucan, and it was most delayed under the influence of OBG. The susceptibility of acidified milk gel to phase separation was significantly influenced by the hydration properties and source of β-glucan. Acidification of gels with the lowest concentration (0.125%) of scleroglucan and OBG promoted aggregation of the caseins and then phase separation. This behaviour was not observed in gels containing linear β-glucan (curdlan). The images acquired under a confocal microscope revealed that the all analysed preparations significantly affected the formation of protein complexes whose size and shape were closely linked with the type of added β-glucan. The morphology of samples containing curdlan most closely resembled the structure of the control gel. The addition (up to 0.5%) of scleroglucan and OBG resulted in a gel with low stability. Separate protein structures and clusters of β-glucan were found. The addition of higher levels of β-glucan resulted in a more homogeneous microstructure of the product, which was similar to the control acidified gels. Graphical abstract: Image 1 Highligths: The structure of β-glucan determine the rheological properties of milk gel. The difference between structure affect the aggregation of milk proteins. The properties of glucan exert an effect on the susceptibility of milk gels stability. The system's stability increased only with higher polysaccharide concentrations. The presented research has important practical implications.